PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI ALFAMART KOTA PALANGKA RAYA - Muhammad Zainal Arifin; Pikri Azhari (AL-QARDH, 2017)
Service quality gives encouragement to consumer to tie a good association with a company. Good service will give an impact to decision of consumer to buy and also to the company itself. A good service quality is very important to create a consumer’s satisfaction, especially in direct proof, capability, attentiveness, and warrant of a consumer’s satisfaction. According to that reasons, so the statement of the problem of this research is the influence of service quality to consumer’s buying decision in Alfamart in Palangka Raya city. This research is using a quantitative approach with survey. A population of this research is consumer of Alfamart in Palangka Raya city. The sample that is taken for this research amounts to 96 respondents which is taken with random sampling. Furthermore, for prequalification test is using normality test with Kolmogorov smirnov and Q-Q plot. Data analysis method is using correlation of product moment and simple regression using SPSS 16. From this study, it is found that the quality of the service and consumer’s buying decision in Alfamart in Palangka Raya city have strong relation according to the result of coefficient of product moment which amounts to 0,810. It is also found the amount of sig that is 0,000 which means there are significant relation. Furthermore, test of simple regression shows the amount of determination of coefficient 0,656 which means the influence of service quality to the consumer’s buying decision is 65,6 %. It is found also the amount of t count which is 13,386 which is bigger than t table, so it can be concluded that service quality has significant influence to consumer’s buying decision.